RANCANG BANGUN APLIKASI RESERVASI TIKET PESAWAT ONLINE BERBASIS ANDROID - Haris Haris; Muhamad Rafi Arfiansyah; Enny Nuraini (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2016)
Ticket reservation of information system is data in physical shape that given bycompany to customers to get service from the company orget the goods which contained in it. And usually in the form of paper ticket that has specific explanation which represented value. The main goal of this research is to design application of aeroplane ticket reservation based on windows phone using DAD (DisciplinedAgileDelivery ) methodology. And it can provide information for people who want travel by air transportation, good information about aeroplane, the flight schedule, and ticket reservation to each destination. Design ticket reservation online based on Android has been successful and implemented with application features such as flight schedules, checking ticket, booking ticket, and register as a member.